The In Vivo study of metal injection moulding 316L stainless steel fracture fixation plate - Mohd Jan, Nurul Hafiza; Zulkifly, Ahmad Hafiz; Buyong, Zunariah; Ibrahim, Mohd Zulfadzli; Sha'ban, Munirah; Omar, Mohd Afian (Trans Tech Publications Ltd., Switzerland, 2016)
In the past few decades, Metal Injection Moulding (MIM) has evolved as a new revolutionary metalworking process for medical implant fabrication in orthopaedics. The technology employs natural resources in a minimum outlay without compromising the quality of its end products. This metalworking process allows the production of a high volume complex prosthetic implants that can be shaped in a single operation and cost productive. In this study, we evaluated the potential of MIM 316L stainless steel as the internal fixation plate in a long bone fracture using rabbit model. The study was approved by the International Islamic University Malaysia Research Ethics Committee. Experimental fractures were made at the rabbits’ tibia and fixed with either MIM plate or AO/ASIF mini plate, as control. The assessments were carried out by means of radiography procedure and histological evaluation at each time point of 3, 6, 9, 12 and 26 weeks post-operatively. Hard tissue processing was used since all samples comprised bone tissue and metal plate. Based on the observation, there were callus formations in both MIM and control groups at week 3 post-operatively. Bone union was evidenced starting week 6, whilst bone remodelling was completed at week 26. Histological assessment indicated that both groups possessed mild to moderate callus bridging at week 3 and week 6, respectively. While complete remodelling bone cortex was evidenced at week 26. Taken together, these findings indicate that the potential of MIM plate to hold the tibial fracture is comparable to that of AO/ASIF plate. Apart from being cost productive, the production of MIM plate also utilizes natural resources. Therefore, the MIM plate can be used as an alternative internal fixator for bone fracture management in orthopaedic.